Synthesis and characterization of laser irradiated polyaniline/rice husk (silica) nanocomposites for electrical conductivity applications - Mezan, Salim Oudah (2023)
Polymer nanocomposites contain inorganic fillers that have metallic particles dispersed in polymer matrices. These are very appealing for optical and electrical conductivity applications. Polyaniline/ silica (rice husk ash CCl (SiO2)), nanocomposites (PANI/RHACCl (SiO2)) nanocomposites can be manipulated through different methods of fabrication for desired purposes. An innovative method for nanocomposite materials fabrication has been developed using sol-gel that has been applied to polyaniline/RHACCl (Silica) nanocomposites. Laser irradiation is also used as a way to manipulate the structure of the nanocomposite to investigate the effect of enhancing new optical and electrical properties. The laser irradiation power of value 13.17 w/cm2 leads to the formation of graphite oxide and carbon percentage increment, which is based on laser irradiation time and distribution percentage of RHACCl nanoparticles. The sodium silicate was obtained using hydrochloric acid (HCl) wash to produce silica. Polyaniline was synthesized by chemical oxidative polymerization, then mixed with RHACCl (SiO2) in the presence of toluene and trimethylamine to form. The samples were analyzed by the structural, chemical, morphology, optical-electrical conductivity, and thermal properties behaviors. The amorphous nature of silica was confirmed using XRD analysis. The sample size was obtained from (6-9 nm) by FESEM morphology studies. EDX atomic weight was measured at 57.10% of carbon, 26. 78% of oxygen, 3.49% of silicon, 10.09% of nitrogen, 0.68% sulfur, and 1.87% of chlorine. UV-Vis absorption wavelength was determined at 382 nm. The best energy band gap of PANI was 1.13 eV and the best laser irradiation time was (40) min. Direct current (DC) electrical conductivity was calculated for the best ratio conductivity values were found to be at PANI / RHACCl (SiO2) NCs after laser irradiation (1: 0.5 = 1.10x10-1 S cm-1, 2: 0.5 = 1.36x10-1 S cm-1 and 3: 0.5 = 2.08x10-1 S cm-1) in the time 40 min